Pengetahuan dan Perilaku Kesehatan Gigi pada siswa SDN 174 Muara Fajar Pekanbaru - Tuti Restuastuti; Handayani Handayani; Yanti Ernalia (Jurnal Ilmu Kedokteran, 2014)
Dental caries and gingivitis are often found in Indonesia primary school students. The data from Puskesmas MuaraFajar noted, only 14.06% of Elementary Students who received dental care and 52% of them required treatment. TheObjective of study was to assess the students’ dental health knowledge and behavior level of SDN 174 Pekanbaruand to associate with dental health status, including dental caries, DMF-T OHI-S, Debris Index (DI-S) and CalculusIndex (CI-S). The methodology used a cross-sectional survey research design. The sample were 61 students whotaken by all students in grade 6 of SDN 174 Muara Fajar Pekanbaru. Examination of student’s dental health statuslike dental caries, DMF-T OHI-S, Debris Index (DI-S) and Calculus Index (CI-S) was made, and followed by askingthe knowledge and behavior questionnaire about dental health. Processed data with the statistical program SPSSversion 17. the data presented in the narrative, univariate analysis to look at the frequency distribution of the data,and bivariate analysis to find an association between the knowledge and behavior to the dental health status. Theresults showed that most characteristics respondents were female (50.8%), aged 12 years (41%) and have enoughnutrition (68.9%). Then there were 25 students (41%) having less knowledge about dental health and as many as 25students (41%) have the less behavior about dental health. While the results of the examination of the dental healthstatus showed as many as 24 students (39%) had problems in the DI-S, 12 students (20%) had problems in the CI-S,and as many as 26 students (43%) had problems in dental health (OHI -S). There was no relationship betweenknowledge of dental health to dental health status, but there is a relationship regarding student behavior of dentalhealth to dental health status(p = 0.02, OR = 3.4).